Actin subversion for productive Plasmodium hepatocyte invasion - Frischknecht, Friedrich; Enninga, Jost (Trends in parasitology, 2023)
Productive invasion of hepatocytes by Plasmodium sporozoites is a key step of infection. The parasites traverse hepatocytes before targeting one of them to form a parasitophorous vacuole for parasite expansion. Schepis et al. show the induction of membrane ruffling via host Rho GTPases by Plasmodium sporozoites facilitating productive invasion.
Online verfügbar 15. März 2023, Artikelversion 12. April 2023
Gesehen am 14.06.2023